PENDEKATAN MAQĀṢID SYARĪ’AH: KONSTRUKSI TERHADAP PENGEMBANGAN ILMU EKONOMI DAN KEUANGAN ISLAM - Fathurrahman, Ayief (State Institute of Islamic Studies (IAIN) Palu, 2014)
ThisÂ article examines the problems that occur in the development process of Islamic economic and finance, both in theory and practice, especiallyÂ in the Islamic banking practice in various parts of the world. To cope with the problems, the maqÄá¹£id al-syarÄ«â€™ah approach can be employed to understand the verses of the Qurâ€™an and the sunnah, to reconsolidate the conflicting arguments, and to decide the legal standing to a case of which legal sanding is not mentioned in the Qurâ€™an and the sunnah. The purpose is to make Islamic economic and finance relevant to the change of time and to reduce the turbulence taking place in the practice of Islamic economy and finance themselves.Kata Kunci : MaqÄá¹£id Syariah, Ekonomi Islam, Pengembangan.